The Association of Obesity with Autoimmune Thyroiditis and Thyroid Function-Possible Mechanisms of Bilateral Interaction - Agnieszka Baranowska-Bik; Wojciech Bik (International Journal of Endocrinology)
A growing number of patients suffer from autoimmune diseases, including autoimmune thyroid disease. There has simultaneously been a significant increase in the prevalence of obesity worldwide. It is still an open question whether adiposity can directly influence activation of inflammatory processes affecting the thyroid in genetically predisposed individuals. Adipokines, biologically active substances derived from the adipocytes, belong to a heterogenic group of compounds involved in numerous physiological functions, including the maintenance of metabolism, hormonal balance, and immune response. Notably, the presence of obesity worsens the course of selected autoimmune diseases and impairs response to treatment. Moreover, the excess of body fat may result in the progression of autoimmune diseases. Nutritional status, body weight, and energy expenditure may influence thyroid hormone secretion. Interestingly, thyroid hormones might influence the activity of adipose tissue as metabolic alterations related to fat tissue are observed under pathological conditions in which there are deficits or overproduction of thyroid hormones. Functioning TSH receptors are expressed on adipocytes. Thermogenesis may presumably be stimulated by TSH binding to its receptor on brown adipocytes. There could be a bilateral interaction between the thyroid and adipose. Obesity may influence the onset and course of autoimmune disease.